HiBiT-SpyTag: A Minimal Tag for Covalent Protein Capture and Degrader Development - Tsang, Tiffany; Huerta, Fidel; Liu, Yingpeng; Che, Jianwei; Metivier, Rebecca J; Ferrao, Silas; Donovan, Katherine A; Jones, Lyn H; Zerfas, Breanna L; Nowak, Radosław P (ACS chemical biology, 2023)
The ability to rapidly and selectively modulate cellular protein levels using small molecules is essential for studying complex biological systems. Degradation tags, such as dTAG, allow for selective protein removal with a specific degrader molecule, but their utility is limited by the large tag size (>12 kDa) and the low efficiency of fusion product gene knock-in. Here, we describe the development of a short 24 amino acid peptide tag that enables cell-based quantification and covalent functionalization of proteins to which it is fused. The minimalistic peptide, termed HiBiT-SpyTag, incorporates the HiBiT peptide for protein level quantification and SpyTag, which forms a spontaneous isopeptide bond in the presence of the SpyCatcher protein. Transient expression of dTAG-SpyCatcher efficiently labels HiBiT-SpyTag-modified BRD4 or IRE1α in cells, and subsequent treatment with the dTAG13 degrader results in efficient protein removal without the need for full dTAG knock-in. We also demonstrate the utility of HiBiT-SpyTag for validating the degradation of the endoplasmic reticulum (ER) stress sensor IRE1α, which led to the development of the first PROTAC degrader of the protein. Our modular HiBiT-SpyTag system represents a valuable tool for the efficient development of degraders and for studying other proximity-induced pharmacology.